Differential effects of dexamethasone on arterial stiffness, myocardial remodeling and blood pressure between normotensive and spontaneously hypertensive rats - Tardelli, Lidieli P. [UNESP]; Duchatsch, Francine [UNESP]; Herrera, Naiara A. [UNESP]; Vicentini, Carlos Alberto [UNESP]; Okoshi, Katashi [UNESP]; Amaral, Sandra L. [UNESP] (Wiley, 2021)
Dexamethasone (DEX)-induced hypertension is observed in normotensive rats, but little is known about the effects of DEX on spontaneously hypertensive animals (SHR). This study aimed to evaluate the effects of DEX on hemodynamics, cardiac hypertrophy and arterial stiffness in normotensive and hypertensive rats. Wistar rats and SHR were treated with DEX (50 μg/kg s.c., 14 d) or saline. Pulse wave velocity (PWV), echocardiographic parameters, blood pressure (BP), autonomic modulation and histological analyses of heart and thoracic aorta were performed. SHR had higher BP compared with Wistar, associated with autonomic unbalance to the heart. Echocardiographic changes in SHR (vs. Wistar) were suggestive of cardiac remodeling: higher relative wall thickness (RWT, +28%) and left ventricle mass index (LVMI, +26%) and lower left ventricle systolic diameter (LVSD, −19%) and LV diastolic diameter (LVDD, −10%), with slightly systolic dysfunction and preserved diastolic dysfunction. Also, SHR had lower myocardial capillary density and similar collagen deposition area. PWV was higher in SHR due to higher aortic collagen deposition. DEX-treated Wistar rats presented higher BP (~23%) and autonomic unbalance. DEX did not change cardiac structure in Wistar, but PWV (+21%) and aortic collagen deposition area (+21%) were higher compared with control. On the other side, DEX did not change BP or autonomic balance to the heart in SHR, but reduced RWT and LV collagen deposition area (−12% vs. SHRCT). In conclusion, the results suggest a differential effect of dexamethasone on arterial stiffness, myocardial remodeling and blood pressure between normotensive and spontaneously hypertensive rats.
Keywords: cardiac hypertrophy; collagen; glucocorticoids; heart rate variability; hypertension; vessel remodeling